SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SISWA OLIMPIADE OLAHRAGA SISWA NASIONAL CABANG SILAT MENGGUNAKAN METODE SAW (SIMPLE ADDITIVE WEIGHTING) - Romi Fabianto Utama; Ari Syaripudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Extracurricular activities are non-formal learning activities carried out by school or university students, generally outside the standard curriculum learning   hours.Extracurricular activities are shown so that students can develop their personality, talents, held from the school and the students themselves to pioneer activities outside of school hours. MTS Muhammadiyah 1 has several extracurricular activities such as futsal, volleyball and silat. Every year there is an O2SN competition, O2SN is an abbreviation of the National Student Sports Olympiad, which is a national event to find new Indonesian seeds in the field of sports, a branch that is competed at O2SN in including athletics, swimming, volleyball, badminton, karate, pencak silat, chess, table tennis. Mts Muhammadiyah Depok, the selection of students who participated in the competition was not well structured, so it was done using DSS (Decicion Support System) with the SAW (Simple Additive Weighting) method. DSS is part of a computer-based information system. Information systems are very important to support decision making, the SAW method is often also known as the sum of the weighted values of the performance rating on each alternative on each attribute. With this system, it will be able to determine who the students are sent to the O2SN silat branch of the competition. This application uses the PHP programming language, MySQL database software and uses the Simple Additive Weighting method and uses UML as a tool to implement the analysis and design process of a decision support system for the selection of national sports olympiad students.